Does IQ explain socioeconomic inequalities in health? Evidence from a population based cohort study in the west of Scotland. Issue 7541 (1st February 2006) - Batty, G David; Der, Geoff; Macintyre, Sally; Deary, Ian J
Abstract: Objective To test the hypothesis that IQ is a fundamental cause of socioeconomic inequalities in health. Design Cross sectional and prospective cohort study, in which indicators of IQ were assessed by written test and socioeconomic position by self report. Setting West of Scotland. Participants 1347 people (739 women) aged 56 in 1987. Main outcome measures Total mortality and coronary heart disease mortality (ascertained between 1987 and 2004); respiratory function, self reported minor psychiatric morbidity, long term illness, and self perceived health (all assessed in 1988). Results In sex adjusted analyses, indices of socioeconomic position (childhood and current social class, education, income, and area deprivation) were significantly associated with each health outcome. Thus the greatest risk of ill health and mortality was evident in the most socioeconomically disadvantaged groups, as expected. After adjustment for IQ, a marked attenuation in risk occurred for poor mental health (range of attenuation in risk ratio across the five socioeconomic indicators: 15-58%), long term illness (25-53%), poor self perceived health (41-56%), respiratory function (44-66%), coronary heart disease mortality (31-111%), and total mortality (45-131%). Despite the clear reduction in the magnitude of these effects after controlling for IQ, in half of the associations examined the risk of ill health in socioeconomically disadvantaged people was still at least twice that of advantaged people. Statistical significance was lost for only 5/25 separate socioeconomic health gradients that showed significant relations in sex adjusted analyses. Conclusions Scores from the IQ test used here did not completely explain the socioeconomic gradients in health. However, controlling for IQ did lead to a marked reduction in the magnitude of these gradients. Further exploration of the currently scant information about IQ, socioeconomic position, and health is needed.